Effect of mineral contents on the growth of vietnamese ginseng (Panax vietnamensis Ha et Grushv.) cultured in vitro photoautotrophically - Ngoc Huong, Ngo Thi; Khiem, Dinh Van; Quynh, Nguyen Thi (Academia Journal of Biology, 2015)
Panax vietnamensis Ha et Grushv. is one of valuable ginseng plants in Vietnam for illness treatment and health maintenance in traditional medicine. With the aim of finding proper culture medium to produce in vitro plants of a high quality, in vitro ginseng shoots, each with an unfolded leaf, were used as explants and cultured photoautotrophically by a natural ventilation method. The culture medium was not supplemented with sucrose, vitamins and plant growth substances. Explants were put into Magenta vessels (V = 370 ml with 2 Millipore filter membranes on each vessel lid) contained 70 ml of one among four different culture media, including full-strength MS, modified MS, Enshi-Shoho or Heller medium. On day 90, ginseng plants cultured on the modified MS medium with a half-strength of both KNO3 and NH4NO3 had better photosynthetic ability and growth when compared with those cultured on the full-strength MS, Enshi-Shoho or Heller medium. The plants also had the greatest increase in plant fresh weight (261,3 mg/plant), dry weight (61,0 mg/plant), the greatest dry weight of rhizomes and roots (51,2 mg/plant) and the largest number of roots (7,6 roots/plants). Ginseng plants, cultured in vitro under photoautotrophic condition, of all treatments showed rhizome formation and development during the culture period.